Covid-19, racismo e sistema penitenciário no Pará: uma análise da atuação do poder judiciário - FARIAS, Carlos Eduardo Salim Lauande (2022)
The object of this work is to investigate how the COVID-19 pandemic affected the prison system in the state of Pará. Therefore, the role of the judiciary in the face of the COVID-19 pandemic in the Pará penitentiary system is delimited as a problem. The first objective was to analyze how the prison system in Brazil is structured based on Critical Criminology. To accomplish this objective, an analysis of the institution of prison was carried out, from the perspective of radical criminology and the historical development of this institution in Brazil, under the theoretical reference of structural racism. The second objective was to study the performance of the Judiciary in the face of the health and economic crisis caused by the COVID-19 pandemic in the Pará penitentiary system, with the theoretical framework of the crisis through a Marxist lens. The third objective was to analyze how the TJPA has acted against the COVID-19 pandemic. Regarding the methodology used in this work, the methods used were deductive and inductive. To extract the concepts from the theoretical framework, the deductive method was used. The analysis of judgments, qualitatively selected according to the scope of the research, was carried out using the inductive method. As for the research techniques, bibliographic review and indirect documentation of judgments were used. A qualitative analysis of the decisions was also carried out and a dialectical counterpoint between the concepts and the researched data was carried out. As a result, it was found that the Brazilian prison system (and, in consequence, the Pará system) is structured by class struggle, racism and patriarchy, in addition to being the stage of countless violence. With the crisis of the COVID-19 pandemic, instead of leniency, these structures and violence were accentuated. As an even more specific result, it was found that the TJPA did not promote any policy to combat COVID 19 within the prisons in Pará; instead, it used the COVID-19 pandemic as a justification for suppressing prisoners' rights.